LINGUOPRAGMATIC ANALYSIS OF MANIPULATIVE DISCOURSE IN ENGLISH AND UZBEK POLITICAL AND MEDIA TEXTS (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the linguopragmatic features of manipulative discourse in English and Uzbek political and media texts. The study treats manipulation as an implicit communicative strategy aimed at influencing the addressee’s perception, evaluation, and interpretation of social reality. The analysis focuses on framing, evaluative vocabulary, metaphorical modelling, presupposition, implicature, modality, rhetorical questions, repetition, and headline compression. English political and media texts tend to employ security, crisis, competition, freedom, and institutional responsibility frames, whereas Uzbek texts frequently activate stability, development, national interest, moral unity, and collective responsibility frames. The article argues that manipulation is not produced by isolated linguistic units alone, but by the interaction of language, context, cultural memory, and audience expectations. The results demonstrate that comparative linguopragmatic analysis helps reveal hidden persuasive mechanisms and contributes to the development of critical media literacy. The findings are relevant for discourse studies, political communication, pragmatics, and comparative linguistics.
Keywords: Manipulative discourse, linguopragmatics, political discourse, media discourse, framing, presupposition, implicature, metaphor, evaluation, pragmatic influence.